Analisis Kebijakan Pencegahan Dan Pengendalian Kebakaran Hutan Dan Lahan Di Provinsi Jambi - Syarifudin; Ardi; Supriyanto (Universitas Jambi, 2018)
The results show that hotspots in Jambi Province in the last 5 (five years) (2011 - 2015) were mostly occurred in Tebo, Muaro Jambi and Sarolangun districts, and there were a close relationship between the enhancement of hotspots with acute respiratory infection people in Jambi Province. The regulations and policies implementationon forest and land fires was weak and needed improvement. The strategy of forest and land fire prevention and control policies are: Increasing the role of law and optimizing the support of central government in overcoming the karhutla disaster; Optimizing the role of regional heads in involving NGOs, communities, and universities in the forest and land fire prevention and control; Strengthen the spatial structuring functionality in the Spatial plans document as an effort to overcome spatial problems; Improving the legislative role in supervision, legislation and budgeting in the prevention and control of forest and land fire; Enforcing law enforcement in the act of violation to the laws and regulations provisions; Improving coordination among institutions and clarifying basic tasks and function of Regional Work Unitand also improving the quality of human resources to overcome the population growth rate and spatial problems.